Students' conceptions of radiation and what to do about them. (8th December 2016) - Plotz, Thomas
Abstract: For good science teaching, it is necessary to have knowledge of your students' preconceptions. Numerous studies have been conducted about typical ideas that students bring to the science classroom in science education research. Unfortunately the domains of which we know preconceptions are not distributed evenly and there is a lack of studies about students' conceptions of electromagnetic radiation. This literature review focuses on the existing body of studies around those conceptions. All studies focusing on conceptions of radiation, including nuclear radiation, have been considered if they were published in international peer reviewed journals in English and German between 1980 and the present day. Some interesting conceptions mentioned in different studies are pointed out, as well as gaps in the literature that need to be filled. At the end, some ideas to conquer misconceptions are presented.